Formulation and Evaluation of Stomach-Specific Bioadhesive Drug Delivery System of Diltiazem Hydrochloride - Patil Mahendra. A; Dr. Nishan N. Bobade; Anuradha S. Khedkar; Nishant P. Deshmukh (Asian Journal of Pharmaceutical Research and Development, 2025)
The present study aimed to develop a stomach-specific bioadhesive tablet of Diltiazem Hydrochloride to achieve controlled and sustained drug release for enhanced bioavailability. The formulation strategy focused on gastroretentive and bioadhesive mechanisms to prolong gastric residence time and improve therapeutic efficacy. Nine formulations (F1–F9) were prepared using varying concentrations of bioadhesive polymers such as chitosan and HPMC K15M, along with excipients like MCC, talc, magnesium stearate, and aerosil.The optimized formulation, F9, exhibited excellent pre-compression and post-compression parameters, with notable bioadhesive strength and a sustained in vitro drug release over 12 hours. It showed a bioadhesive retention time of 12 hours and followed zero-order drug release kinetics, ensuring a steady release independent of drug concentration. This prolonged gastric retention enhances drug absorption at its preferred site, addressing limitations of conventional formulations such as low bioavailability and frequent dosing.The study concludes that the bioadhesive tablet system of Diltiazem Hydrochloride is a promising approach for improving patient compliance and achieving consistent therapeutic effects. The formulation offers potential for scale-up and application to other drugs with similar absorption characteristics.